Electronically Tunable Filters - Wong, Peng Wen (IEEE, 2009)
In this article, a brief introduction to the development of tunable filters was given. A classical design technique based on a combline filter approach was shown, where minimum degradation in passband performance could be obtained across a broad-tuning range. The fundamental disadvantages associated with the conventional resonator tuning approaches were also discussed, recognizing the importance of developing new techniques for realizing tunable microwave filters. It was shown that there is a possibility in realizing an electronically reconfigurable microwave filter based on parallel- coupled switched-delay lines, which possesses the important property of maintaining constant absolute bandwidth over almost an octave of tuning bandwidth. Furthermore, the filter has the ability to incorporate active switching elements in the filter circuit, without sacrificing its loss and linearity performance. With the exceptional linearity performance and power handling capability, the filter is readily adapted to poor environments. Although the use of p-i-n diodes as switching elements would result in large dc consumption, the approach could also be readily adapted for use with any switches, such as pHEMT or RF MEMS switches, to achieve extremely low power consumption. The integration of switchable couplings to enable both bandwidth and center frequency to be reconfigurable would be an enhancement.